Transition and challenge : China's population at the beginning of the 21st century - Zhao, Zhongwei (ed.); Guo,Fei (Ed.) (New York, 2007)
With the largest population in the world, China has experienced significant demographic, social, and economic changes in recent decades. Extraordinary demographic changes took place in China in the second half of the twentieth century having wide-ranging consequences. This book, written by a group of leading experts, examines these profound changes in an effort to understand their long term impact and provide an up-to-date account of China's demographic reality. The volume provides a comprehensive and authoritative analysis of a wide range of issues such as China's unprecedented family planning program, the impact of falling birth rates coupled with increasing life expectancy, changes in marriage patterns, and increasing rural-urban migration. Anyone who is interested in China and its recent demographic changes will benefit from the rich materials and thorough analysis provided in this book.
Keywords: Population-China